Activation and IL-10 production of specific CD4+ T cells are regulated by IL-27 during chronic infection with Plasmodium chabaudi. (February 2020) - Sukhbaatar, Odsuren; Kimura, Daisuke; Miyakoda, Mana; Nakamae, Sayuri; Kimura, Kazumi; Hara, Hiromitsu; Yoshida, Hiroki; Inoue, Shin-Ichi; Yui, Katsuyuki
Abstract: IL-27, a regulatory cytokine, plays critical roles in the prevention of immunopathology during Plasmodium infection. We examined these roles in the immune responses against Plasmodium chabaudi infection using the Il-27ra −/− mice. While IL-27 was expressed at high levels during the early phase of the infection, enhanced CD4 + T cell function and reduction in parasitemia were observed mainly during the chronic phase in the mutant mice. In mice infected with P. chabaudi and cured with drug, CD4 + T cells in the Il-27ra −/− mice exhibited enhanced CD4 + T-cell responses, indicating the inhibitory role of IL-27 on the protective immune responses. To determine the role of IL-27 in detail, we performed CD4 + T-cell transfer experiments. The Il-27ra −/− and Il27p28 −/− mice were first infected with P. chabaudi and then cured using drug treatment. Plasmodium- antigen primed CD4 + T cells were prepared from these mice and transferred into the recipient mice, followed by infection with the heterologous parasite P. berghei ANKA. Il-27ra −/− CD4 + T cells in the infected recipient mice did not produce IL-10, indicating that IL-10 production by primed CD4 + T cells is IL-27 dependent. Il27p28 −/− CD4 + T cells that were primed in the absence of IL-27 exhibited enhanced recall responses during the challenge infection with P. berghei ANKA, implying that IL-27 receptor signaling during the primary infection affects recall responses in the long-term via the regulation of the memory CD4 + T cell generation. These features highlighted direct and time-transcending roles of IL-27 in the regulation of immune responses against chronic infection with Plasmodium parasites. Graphical abstract: Unlabelled Image Highlights: IL-27 is mainly produced during the acute phase of malaria infection. IL-27 inhibits the immune response during chronic malaria infection. IL-27 in the primary infection affects the recall responses of CD4 + T cells. IL-10 production by Plasmodium -primed CD4 + T cells is IL-27 dependent.